Effects of the new fasting standard on sedation in the pediatric emergency room. Issue 1 (4th January 2022) - Hara, Yutaro; Hagiwara, Yusuke; Inoue, Nobuaki
Abstract: Background: This study compared adherence to the fasting‐time guidelines of the International Committee for the Advancement of Procedural Sedation (ICAPS) and the North American Society of Anesthesiologists (ASA) and complication rates in pediatric patients requiring procedure sedation and analgesia during treatment in the emergency room (ER). Methods: This retrospective, single‐center study was performed between 2016 and 2020, and enrolled patients who received procedural sedation and analgesia in the ER with the fasting times recommended in the ICAPS and ASA guidelines. Results: In total, 857 patients were included. The most frequent indication for procedural sedation and analgesia was fracture reduction in 420 patients (49.0%). Ketamine, the most commonly administered drug, was given to 710 patients (82.8%). Adherence to the ICAPS guidelines was higher ( P < 0.01), with 772 (95.7%) and 351 (41.0%) patients, respectively, adhering to the ICAPS and ASA recommendations for food and drink fasting times. Complications occurred in 130 patients (15.2%), including SpO2 <90% in 75 patients (8.7%) and vomiting in 20 patients (2.3%). No serious complications, such as aspiration, cardiac arrest, or death, occurred. The complication rate between the two groups did not differ significantly, with 50 (14.2%) and 127 (15.5%) patients experiencing complications according to the ICAPS and ASA guidelines, respectively ( P = 0.586). Conclusions: The fasting recommendations of the ICAPS guidelines, which propose risk stratification to determine the appropriate fasting time for procedural sedation and analgesia, are more tolerable to patients and the rate of adverse events did not appear to be different from that experienced when following the ASA guidelines.